Wanprestasi dalam Perjanjian Kredit Pemilikan Rumah (KPR) pada Bank Tabungan Negara Kantor Cabang Solo - Clarissa Vania Verianti; Noor Saptanti (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
Bank Tabungan Negara Branch Office Solo (Bank BTN KC Solo) is an extension of the main BTN bank that carries out tasks and business activities in the field of financial banking services, especially in supporting financing in the housing sector through providing BTN mortgage facilities (KPR BTN). One of the issues that arise in providing these KPR facilities is default or breach of promise due to the non-payment of installments in the KPR. The purpose of this research is to determine the procedures for implementing BTN mortgage facilities and to identify solutions to problems in providing BTN mortgage facilities. The type of research used is normative-empirical legal research, using descriptive research, with a live case study approach. Data is based on primary and secondary data, with data analysis techniques used in this study being interactive analysis models. The results indicate that if a debtor defaults, the legal consequences for the bank are the right to contact the debtor and/or other relevant parties and the right to issue warnings in the form of default notices in the form of letters or similar deeds. The efforts made by the bank against debtors who default include collection efforts, credit salvage efforts, and credit resolution efforts.